DETERMINATION OF SILICA POLYMORPHS AND FELDSPARS IN INDUSTRIAL SAMPLES OF BENTONITE AND PERLITE - Kaza, T.; Stamatakis, M.G. (Bulletin of the Geological Society of Greece, 2016)
The aim of the present study is to apply a fast and reliable XRD method to identify the percentage of silica polymorphs and feldspars that industrial bentonite and perlite may contain, because these gangue minerals influence the quality of the final products. The current research was implemented by selecting of appropriate almost pure reference samples of bentonite and perlite in which specific amount of silica polymorphs and feldspars was added. The selection of all samples was based on the X-ray diffraction patterns. The synthetic mixtures produced were either with bentonite or perlite with a single added mineral or with two of them in percentages up to 10%. The minerals added to the reference samples were distinguishable in the XRD patterns in different percentages for each mineral added, but also in the two different reference samples. After evaluating of the XRD patterns of a series of samples, it was concluded that the lowest percentage of silica polymorphs and albite that was detected in the reference bentonite was 0.5% quartz, 1% cristobalite 10% opal CT, and 1% albite, whereas the percentages for the reference perlite was 1% quartz, 2% opal-CT, 1% cristobalite and 0.5% albite. This method can beapplied to any commercial bentonite and perlite bulk sample to define its purity concerning its silica polymorph and feldspar content.